Produksi Eco Enzyme dengan Pemanfaatan Limbah Rumah Tangga untuk Menjaga Kesehatan Masyarakat di Era New Normal - Rida Jelita (Jurnal Maitreyawira, 2022)
ABSTRACT By utilizing household waste which was usually useful as a substitute for industrial chemical products. Not only for environment, household waste could create economic value for Buddhists in PBSM Pekanbaru because besides being clean the environment also did not require expensive costs to obtain it. By introducing Eco Enzyme household waste management. This Community Service aims to provide Buddhist Eco Enzyme making training with Utilization of Household Waste at the PBSM Pekanbaru. So that Buddhists at PBSM know about the meaning and how to made Eco Enzyme and know the benefits of household waste and other types of household waste.There were several results that are considered as a result of the mentoring activities in the training of making Eco Enzyme with the use of household waste for Buddhists at PBSM Pekanbaru during this service. Among the results deemed to be the result of assistance are as follows: Showing the satisfaction of various parties and becomes an indicator of the success of this service program, Judging from the process during the mentoring activity, it was found that there was enthusiasm from the participants have better understanding in making Eco Enzyme, There were opinions, positive comments and good hoped from the PBSM Leader, and as training participants, they hope that similar activities will always be held for the following years